Cathepsin D and apoptosis related proteins are elevated in the brain of autistic subjects - Sheikh, A.M.; Li, X.; Wen, G.; Tauqeer, Z.; Brown, W.T.; Malik, M. (Neuroscience, 2010)
Autism is a severe neurodevelopmental disorder characterized by problems in communication, social skills, and repetitive behavior. Recent studies suggest that apoptotic mechanisms may partially contribute to the pathogenesis of this disorder. Cathepsin D is the predominant lysosomal protease and is abundantly expressed in the brain. It plays an important role in regulation of cellular apoptosis and has been shown to mediate apoptosis induced by cytokines tumor necrosis factor (TNF)-α and interferon (IFN)-γ. In this study, we examined the expression levels of cathepsin D in the autistic brain. We found that cathepsin D protein expression was significantly increased in the frontal cortex, in pyramidal and granule cells of the hippocampus, and in cerebellar neurons in autistic subjects as compared to controls. In addition, we found that the expression of the anti-apoptotic protein Bcl-2 was significantly decreased, while caspase-3, a critical executioner of apoptosis, was increased in the cerebellum of autistic subjects. Previously our studies have shown that Bcl-2 expression is decreased and the BDNF-Akt-Bcl-2 pathway is compromised in the frontal cortex of autistic subjects, which suggested that increased apoptosis may be involved in the pathogenesis of autism. Our current finding of decreased Bcl-2 and increased capase-3 in the cerebellum of autistic subjects further supports this suggestion. In addition, the finding of increased cathepsin D in the cerebellum of autistic subjects suggests that, through its regulation of apoptosis, the altered activities of cathepsin D in the autistic brain may play an important role in the pathogenesis of autism.